Utilização de imagens mentais na prática diária de estudantes do bacharelado em violão da UFPB - Donoso, Pablo Pérez (2014)
Music education has undergone a number of changes in recent centuries. These changes do not happen in isolation but interact and are interdependent events with another knowledge areas. Dominant paradigm in musical instrument teaching, since the establishment of music education model appeared at eighteenth century conservatorie, has roots in Newtonian-Cartesian thinking. Nowadays can be observed a change of mindset from almost all areas, is the rise of new paradigms fleeing from fragmentation, mechanization and mind-body dissolution that the old paradigm suggests, these new paradigms are heading to a holistic and integrative vision. The aim of this study was to observe and analyze imagery utilization in guitar student's daily practice, as it considered them a key component in these emerging paradigms. Data were gathered with three UFPB bachelor's guitar students. Were observed the student's study routines, data analysis gave the understanding of the current state of the relationship and interactions between knowledge of the cognitive sciences and the musical instrument teaching / learning process in our context today.